OP06 Primary care clinicians' confidence, willingness and participation in advance care planning discussions: a multi-site survey. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Howard, M; Bernard, C; Slaven, M; Tan, A; Barwich, D; Klein, D; Heyland, D
Abstract : Background: People who engage in advance care planning (ACP) are more likely to receive healthcare that is concordant with their goals and wishes at the end of life. Primary care providers are ideally positioned to facilitate ACP. This study sought to describe the confidence, willingness and participation of primary care clinicians to have advance care planning discussions. Methods: We conducted a survey of family physicians and allied health professionals (AHP)in primary care in three Canadian provinces. We asked about willingness and confidence to have ACP discussions and current participation on Likert-type scales (0=not at all, 6=an extreme amount). A modified Dillman approach was used for online survey administration. Results: The response rate was 72% (n=117) among physicians and 69% (n=62) among allied health professionals. Most physicians (77%) were practicing in an interprofessional practice. The mean willingness to initiate ACP was 5.0 for physicians and 4.8 for AHP. Mean confidence ratings for initiating ACP was 4.8 for physicians and 3.5 for AHP. Current participation in ACP among patients aged 50 years and older was lower; 2.6 for physicians and 1.4 for AHP. Conclusions: The willingness of family physicians and AHP in primary care to initiate ACP discussions with patients is high. However, confidence is only moderate in AHP and actual activity is low for all clinicians. Efforts to remove barriers in primary care and provide support for AHP to improve their confidence to engage in ACP discussions should be priorities.